Managerial Competence Development of Future Physical Education Professionals through Hybrid Educational Environments - Chen, Ronghao (Педагогічна Академія: наукові записки, 2025)
The aim of the study is to determine the effectiveness of hybrid and blended learning in physical education for students, with an emphasis on the development of physical activity, cognitive abilities and psychological resilience in the context of digital transformation of education. Methods. The study used a comprehensive approach that included analysis of theoretical sources, modeling of educational processes, student questionnaires, and observation of the dynamics of their physical activity, motivation, and level of involvement in the educational process. Comparative analysis methods were also used to evaluate the effectiveness of traditional and hybrid learning formats. Results. It was found that the introduction of hybrid learning in physical education contributes to increasing the level of physical activity of students, forming independent work skills and improving cognitive performance. The mixed format allows for the more effective adaptation of educational programs to the individual needs of students, contributing to a reduction in stress levels, improved motivation to study and an improvement in the overall psycho-emotional state. It was found that the combination of face-to-face and distance learning components provides greater flexibility in the learning process while maintaining a high level of student engagement in educational activities. It was noted that students who studied under the hybrid model demonstrated higher levels of self-regulation, responsibility, and ability to plan their own physical activity. Conclusions. Hybrid and blended learning in physical education are effective strategies for developing physical activity and cognitive and psychological skills of students in the context of the digitalization of education. The implementation of such models improves the quality of the educational process, promotes the formation of health-saving behavior and the development of competencies necessary in modern society. To maximise the positive effect, it is necessary to further improve methods for integrating health-saving technologies, individualising educational programs and ensuring access to digital resources for all participants in the educational process.